Genome sequencing analysis of a novel thermophilic strain Geobacillus sp. CX412 - Li, Xin; Zhang, Wei; Zhong, Xin-Ru; Han, Hao-Xuan; Dong, Bin (Frontiers in Microbiology, 2022)
The thermophilic spore-forming strain Geobacillus sp. CX412 was isolated from hot spring soil in Tengchong City, Yunnan Province, China. We sequenced the complete genome of Geobacillus sp. CX412 using PacBio SMRT Sequencing. Genome-scale phylogenetic analysis and average nucleotide identity (ANI) results indicated that Geobacillus sp. CX412 is a novel species in the genus Geobacillus. The metabolic potential of Geobacillus sp. CX412 based on COG, KEGG, and CAZymes analysis demonstrated that Geobacillus sp. CX412 was a highly adaptable strain with an unusually high number of 73 annotated transposons in the genome, which is relatively rare in Geobacillus. Compared with the near-derived strains, it was found that Geobacillus sp. CX412 has the unique β-lactam resistance and more active metabolism (more than 50.5%-100.1%). Additionally, its genome encodes glycoside hydrolases and other genes related to lignocellulose breakdown, suggesting that Geobacillus sp. CX412 has a considerable biomass degradation potential. Thus, Geobacillus sp. CX412 is a new thermophilic bacterial species that add to the increasing repertoire of known lignocellulose degraders.